2017
DOI: 10.1371/journal.ppat.1006256
|View full text |Cite
|
Sign up to set email alerts
|

Integrated systems biology analysis of KSHV latent infection reveals viral induction and reliance on peroxisome mediated lipid metabolism

Abstract: Kaposi’s Sarcoma associated Herpesvirus (KSHV), an oncogenic, human gamma-herpesvirus, is the etiological agent of Kaposi’s Sarcoma the most common tumor of AIDS patients world-wide. KSHV is predominantly latent in the main KS tumor cell, the spindle cell, a cell of endothelial origin. KSHV modulates numerous host cell-signaling pathways to activate endothelial cells including major metabolic pathways involved in lipid metabolism. To identify the underlying cellular mechanisms of KSHV alteration of host signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 100 publications
1
65
0
Order By: Relevance
“…To our knowledge, only few publications describe global cellular changes after viral infection focusing on the expression and regulation of protein-coding as well as ncRNA genes. A recent report studied the host transcriptome and proteome during KSHV infection and identified global changes in the cellular networks that are essential for virus latency (Sychev et al, 2017). The authors identified alterations in approximately 17 % of the host transcriptome and 13 % of the cellular proteome that includes also dramatic changes in the phosphoproteome 48 hours after KSHV infection.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only few publications describe global cellular changes after viral infection focusing on the expression and regulation of protein-coding as well as ncRNA genes. A recent report studied the host transcriptome and proteome during KSHV infection and identified global changes in the cellular networks that are essential for virus latency (Sychev et al, 2017). The authors identified alterations in approximately 17 % of the host transcriptome and 13 % of the cellular proteome that includes also dramatic changes in the phosphoproteome 48 hours after KSHV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Human herpesvirus-8, also known as Kaposi sarcoma-associated herpesvirus, is another member of the herpesviridae family best known for its association with Kaposi sarcoma (KS). HHV-8 has also been implicated in two B-cell lymphoproliferative diseases, multicentric Castleman disease (MCD) and primary effusion lymphoma (PEL) [ 83 ]. Viral transmission occurs via salivary, blood, and sexual contact; mother-to-fetus transmission is rare [ 84 ].…”
Section: Human Herpesvirus-8mentioning
confidence: 99%
“…Similarly, the cucumber necrosis virus (CNV) induces the formation of peroxisomal vesicles in which the viral RNA replication occurs in yeast cells [117]. Studies revealed upregulation of peroxisomal biogenesis in endothelial cells upon latent infection of Kaposi's sarcoma associated herpes virus [118]. It was also reported that proteins involved in peroxisomal lipid metabolism were essential for the survival of latently infected human dermal microvascular endothelial cells and lymphatic endothelial cells [118].…”
Section: Effect On Peroxisome Morphology/biogenesismentioning
confidence: 99%
“…Studies revealed upregulation of peroxisomal biogenesis in endothelial cells upon latent infection of Kaposi's sarcoma associated herpes virus [118]. It was also reported that proteins involved in peroxisomal lipid metabolism were essential for the survival of latently infected human dermal microvascular endothelial cells and lymphatic endothelial cells [118]. Interestingly, HIV infection reduces the number of peroxisomes in infected cells due to upregulation in the levels of microRNAs that inhibit production of peroxisome biogenesis factors [119].…”
Section: Effect On Peroxisome Morphology/biogenesismentioning
confidence: 99%